Niger : Public Expenditure and Financial Accountability (PEFA) Assessment. (IMF Staff Country Reports; Country Report ;, 2013)
This paper provides details of Public Expenditure and Financial Accountability (PEFA) Assessment report for Niger. The measurement of the public financial management performance indicators shows that progress has been insignificant. Reform programs in progress in the area of oversight and external auditing are moving ahead; as this trend continues, the progress will be reflected in the scores of subsequent assessments. However, the progress of the external audit will continue to depend on positive trends in the area of accounting, information recording, and financial reporting.